PIWI-piRNA pathway: Setting the pace of aging by reducing DNA damage - Lenart, Peter; Novák, Jan; Bienertova-Vasku, Julie (Mechanisms of ageing and development, 2018)
Transposable elements (TEs) are powerful drivers of genome evolutionary dynamics but are principally deleterious to the host organism by compromising the integrity and function of the genome. The transposition of TEs may result in mutations and DNA damage. DNA double-strand breaks (DSBs), which may be caused by the transposition, are one of the processes directly linked to aging. TEs may thus be considered to constitute an internal source of aging and the frequency of transposition may, in turn, be considered to affect the pace of aging. The PIWI-piRNA pathway is a widespread strategy used by most animals to effectively suppress transposition. Interestingly, the PIWI-piRNA pathway is expressed predominantly in the animal germline, a more or less continuous immortal lineage set aside after the first few cell divisions of a developing embryo. Recent findings further imply that the PIWI-piRNA pathway and TE suppression constitute an important mechanism regulating aging. This article discusses the proposed role of the PIWI-piRNA pathway in setting the pace of aging as well as the possible mechanisms underlying this process.
Keywords: poškození DNA; Argonaut proteiny; buněčné dělení; Aging; Animals; Argonaute Proteins; DNA Damage; lidé; Humans; RNA, Small Interfering; zvířata; malá interferující RNA; Cell Division; stárnutí